Synthesis and Characterization of Gellan Gum Based Bioadsorbent for Wastewater Treatment - Giri, Tapan K.; Yadav, Bhupendra K.; Badwaik, Hemant (Current Microwave Chemistry, 2018)
Background: Expand of industrial activity elevates the question of waste water treatment containing heavy metal ions. Removal of lead ions from industrial wastewater has immense scientific and practical interest. Adsorption is a promising technique due to its easy handling, high efficiency, and availability of different adsorbents. Graft copolymerization of natural polysaccharides is becoming a very important resource to develop superior materials for adsorption of heavy metals. Methods: In this study, graft copolymer of gellan gum and polyacrylamide was synthesized by a microwave-assisted method using a very low concentration of potassium persulphate for the biosorption of Pb++ ions from aqueous solution. Fourier transform infrared spectroscopy, scanning electron microscopy, x-ray diffraction, and differential scanning colorimetry were used to characterize the graft copolymer. Results: The optimum grafting was observed when the reaction mixture containing 20 x10-3 mol/L potassium persulphate; 71.42g/L polyacrylamide and 10.71g/L gellan gum, when exposed to 800W microwave power for 120s. The sorption process is pH dependent and maximum sorption was obtained at pH 5. The sorption data were found to obey both Langmuir and Freundlich sorption isotherms but Langmuir isotherm proved to be a better mathematical fit for equilibrium data than Freundlich model. A metal capped structure was observed by SEM analysis after Pb++ ions biosorption. Conclusion: Present study concluded that microwave assisted synthesized gellan gum based bioadsorbent has potential to be used in wastewater treatment.
Keywords: potassium persulphate